2021
DOI: 10.1177/14613484211040318
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic stressed microbeam analysis based on Moore–Gibson–Thompson heat equation and laser excitation resting on Winkler foundation

Abstract: In this work, a modified viscoelastic model of initially stressed microbeam on the base of the Winkler foundation under the effect of ultrafast laser heating and axial stress has been proposed. Viscosity effects are taken into account following the Kelvin–Voigt model. The governing equation for the thermoelastic vibration of the microbeam is obtained when the thermal field effect is defined by the non-Fourier Moore–Gibson–Thompson (MGT) heat equation. The microbeam is seen as an Euler–Bernoulli beam that is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The CVA is the acronym for computational vibrational analysis. Because the CVA plays such an important role in the extraction of electrical power, it is necessary to provide a comprehensive description of the issue [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Exergy Based Results and Discussion On Pveh Based Energy Systemmentioning
confidence: 99%
“…The CVA is the acronym for computational vibrational analysis. Because the CVA plays such an important role in the extraction of electrical power, it is necessary to provide a comprehensive description of the issue [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Exergy Based Results and Discussion On Pveh Based Energy Systemmentioning
confidence: 99%
“…This model elucidates the manner in which an elastic material reacts to stress under conditions where deformation is time-dependent yet reversible. Many investigators worked on the different problems of viscoelastic and thermo-viscoelastic such as [19][20][21][22][23][24][25][26]. Lotfy and his team conduct extensive research on problems related to piezothermoelastic media with photothermal effects, focusing on the hyperbolic twotemperature model [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the fluid velocity of the fluid flowing in the pipe on a Winkler foundation is greater than the one in the pipes with no foundation [4]. A two-parameter foundation model -the Pasternak-Winkler was recently applied in the study of vibration in pipelines for conveying fluid [8], while some others have applied the viscous model which is an extension of the Winkler's model for polymer rubber sheet to explain the effect of time dependence [9]. The fluid conveying pipe problems have been studied using a variety of solution techniques most of which are numerical methods.…”
Section: Introductionmentioning
confidence: 99%